16S rDNA Typing of Salmonella Typhi Strains from Different Geographical Locations in Sumba Island East Nusa Tenggara Indonesia (Microbiology Indonesia, 2013)
A total of thirteen isolates representative of Salmonella Typhi from different geographical locations in Sumba Island, East Nusa Tenggara, Indonesia were identified by 16S rDNA gene sequences. Bacterial DNA extraction was prepared by using a PurelinkTM Genomic DNA kit. The bacterial DNA and control were amplified using the specific primers for S. Typhi. These 16S rDNA gene sequence data were aligned with the corresponding available S. Typhi sequence and the reference organisms from the family Enterobacteriaceae from NCBI database by using the CLUSTAL X software. Phylogenetic trees were generated using the PHYLIP software package and the matrix of nucleotide similarity and nucleotide difference were generated by using the PHYDIT software. The results from the 16S rDNA analysis showed that the degree of similarity within these strains ranged from 99.13-100%. The percentage of sequence similarity between S. Typhi strains was very high (>99 %). Molecular phylogenetic analysis showed that all of the isolates formed a new center of diversity with S. Typhi ATCC 19430T as a reference strain. Based on these results, all of the tested strains belonged to species of S. Typhi suggested by their relatedness with the type strain of S. Typhi ATCC 19430T.